Design and Experimental Testing of a Solar Box Cooker with Paraffin Wax as Thermal Energy Storage Using Maiduguri Weather Condition - Maina, M. B.; Shodiya, S.; Abdulrahim, A.T. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
The performance of paraffin wax as phase change material (PCM) for thermal energy storage (TES) was investigated using a Solar Box Cooker (SBC) exposed to Maiduguri weather condition. Temperature and energy generated by SBC were experimentally established. The result shows tremendous improvement in energy storage compared to SBCs without TES in existence within Maiduguri and environs. The measured temperature and energy generated by the PCM in the experiment were 118oC and 4164.5KJ respectively, an adequate temperature and energy for cooking during off-sunshine hours and beyond. First figure of merit (F1) and second figure of merit (F2) were deduced to be 0.13 and 0.44 with overall SBC efficiency (ɳ) of 63% qualifying the SBC to grade A based on the Bureau of Indian Standards (BIS)